Seeing the big picture in services marketing research: infographics, SEM and data visualisation. Issue 6 (14th September 2015) - Ashman, Rachel; Patterson, Anthony
Abstract : Purpose: – This paper aims to present a way to make structural equation modelling (SEM) studies more accessible and impactful. This paper suggests that authors service readers by translating their work into an infographic that clearly and artfully illustrates the essence of a paper's contribution. Design/methodology/approach: – Through the presentation of a worked example, this paper outlines four service components needed to create a visually striking, yet informative, infographic. Findings: – This paper contends that authors who follow this approach will improve the marketability of their research without oversimplifying or "dumbing down" its insights. Research limitations/implications: – Until a journal editor insists that modellers undertake some translation of their results as a pre-requisite to publication, this paper is unlikely to herald a revolution in how quantitative work is communicated. Practical implications: – This fresh thinking can offer a way for practicing managers, and other marketing researchers unfamiliar with SEM's peculiarities, to comprehend the findings of such studies. Originality/value: – This paper contributes to a nascent body of research on how to effectively disseminate research findings to a broader audience through adopting a service arts perspective and presents an interpretive view of quantitative research never seen before in the pages of this journal.